‘One Nearly Landed On My Finger’: A Forest Kindergarten In Rural New Zealand - Dylan Braithwaite (New Zealand Journal of Teachers' Work)
Once a week, since March of this year, ten four-year-old children, their teacher and at least two parent helpers depart the kindergarten at 9:00 am and leave for a day in the ‘forest’. After a few minutes walk the group make basecamp at O’Connor’s Bush Reserve, in the small rural Wairarapa town of Greytown, and the reserve becomes the context for the kindergarten day. The Forest Kindergarten programme has its antecedents in extensive work undertaken by the teaching team under the general heading of ‘sustainability’. The following is a description of our sustainability story and the development of our Forest Kindergarten programme. I describe what a Forest Kindergarten day looks like, and include some early findings from our first experiences with the children in the bush. The teaching team feel the Forest Kindergarten programme compliments the sustainability focus, helping to re-connect children with nature in a real and practical way.